Metabolomic Assay, Computational Screening, and Pharmacological Evaluation of Caulerpa racemosa as an Anti-obesity With Anti-aging by Altering Lipid Profile and Peroxisome Proliferator-Activated Receptor-γ Coactivator 1-α Levels - Permatasari, Happy Kurnia; Nurkolis, Fahrul; Hardinsyah, Hardinsyah; Taslim, Nurpudji Astuti; Sabrina, Nindy; Ibrahim, Faisal Maulana; Visnu, Jodi; Kumalawati, Dian Aruni; Febriana, Sri Awalia; Sudargo, Toto; Tanner, Melvin Junior; Kurniatanty, Isma; et al. (Frontiers in Nutrition, 2022)
Obesity is associated with an accelerated aging process, which prevents healthy aging. Both obesity and aging were manifested in the peroxisome proliferator-activated receptor-γ coactivator α (PGC-1α) level. These studies fulfill the scientific gap in assembled pharmacological activity assay of Caulerpa racemosa done in a previous preclinical trial. Six major compounds from sea grape (C. racemosa) extract were evaluated using an in silico approach against human pancreatic lipase, a-glucosidase, and a-amylase to predict prospective anti-obesity candidates. The lipase inhibitory activity of the extract reached 90.30 ± 0.40%, 1.75% lower than orlistat. The a-amylase inhibitory assay of the extract was 84.07 ± 5.28%, while the inhibitory activity against a-glucosidase was 81.67 ± 1.54%; both were lower than acarbose. We observe the effect of C. racemosa extract as anti-obesity with anti-aging by evaluating the obesity parameters in the human body for a 4-week period. There was a significant decrease in blood glucose, total cholesterol, low-density lipoprotein (LDL), triglycerides (TG), waist circumference, waist-hip ratio, and body weight (p < 0.05); PGC-1α and high-density lipoprotein (HDL) increased significantly (p = 0.000), in Group B when compared with Group A. Our study revealed that sea grape extract is a potent anti-obesity with an anti-aging reagent that does not produce any significant adverse effects.